Subnational Taxation in Developing Countries : A Review of the Literature - Bird, Richard M. (2012)
This paper reviews the literature on tax assignment in decentralized countries. Ideally, own-source revenues should be sufficient to enable at least the richest subnational governments to finance from their own resources all locally-provided services that primarily benefit local residents. Subnational taxes should also not unduly distort the allocation of resources. Most importantly, to the extent possible subnational governments should be accountable at the margin for financing the expenditures for which they are responsible. Although reality in most countries inevitably falls far short of these ideals, nonetheless there are several taxes that subnational governments in developing countries could use to help ensure that decentralization yields more of the benefits it appears to promise in theory. At the local level, such taxes include property taxes and, especially for larger cities, perhaps also a limited and well-designed local business tax. At the regional level, in addition to taxes on vehicles, governments in some countries may be able to utilize any or all of the following -- a payroll tax; a simple surcharge on the central personal income tax; and a sales tax, in some cases perhaps taking the form of a well-designed regional value-added tax. The "best" package for any particular country or subnational government is likely to be not only context-specific and path-dependent, but also highly sensitive to the balance struck between different political and economic factors and interests.